2018
DOI: 10.1186/s12879-018-3384-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between unhygienic menstrual management practices and prevalence of lower reproductive tract infections: a hospital-based cross-sectional study in Odisha, India

Abstract: BackgroundThe extent to which reproductive tract infections (RTIs) are associated with poor menstrual hygiene management (MHM) practices has not been extensively studied. We aimed to determine whether poor menstrual hygiene practices were associated with three common infections of the lower reproductive tract; Bacterial vaginosis (BV), Candida, and Trichomonas vaginalis (TV).MethodsNon-pregnant women of reproductive age (18–45 years) and attending one of two hospitals in Odisha, India, between April 2015 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
168
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(181 citation statements)
references
References 40 publications
6
168
2
5
Order By: Relevance
“…Measures assessing the type of material used do not reveal if this material was preferred, just as those capturing the quantity of materials used do not indicate if the user felt this was sufficient. Practices may be classified as more favourable based on their associations with reproductive tract infections, [15] but the usefulness of these categories is limited when considering program impacts on other outcomes such as menstrual experience, psychosocial wellbeing or social participation. We hypothesise that measures of individuals' perceived adequacy of practices and environments are likely to more closely align with findings from qualitative research and predict social participation and wellbeing, as they acknowledge that the same practices may be appraised differently due to a range of individual and sociocultural influences.…”
Section: Menstrual Practice Needsmentioning
confidence: 99%
“…Measures assessing the type of material used do not reveal if this material was preferred, just as those capturing the quantity of materials used do not indicate if the user felt this was sufficient. Practices may be classified as more favourable based on their associations with reproductive tract infections, [15] but the usefulness of these categories is limited when considering program impacts on other outcomes such as menstrual experience, psychosocial wellbeing or social participation. We hypothesise that measures of individuals' perceived adequacy of practices and environments are likely to more closely align with findings from qualitative research and predict social participation and wellbeing, as they acknowledge that the same practices may be appraised differently due to a range of individual and sociocultural influences.…”
Section: Menstrual Practice Needsmentioning
confidence: 99%
“…The most obvious advantage of disposable sanitary pads is hygiene. If reused cloths are not washed and dried properly or washed with unclean water, they can cause vaginal infections and harmful diseases (Das et al, 2015;Torondel et al, 2018), which may prevent participation in the workforce due to bad health. Another important advantage of sanitary pads, in particular in environments where menstruating women are socially stigmatized, is that their use is less visible and that they are less subject to leakage.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, about 53.6 %( 95% CI: 48.5, 58.6) of the school females MHM practice was unsafe. This finding is lower when compared to studies conducted in Bahir Dar, in Nekemte, Ethiopia, and in Uganda in 2014/15 among school girls, in which the prevalence of unsafe MHM practice was 75.5%, 60%, and 90.5% respectively (7,13,14). The observed difference in prevalence could be due to the difference in the year of the study period.…”
Section: Discussionmentioning
confidence: 56%
“…Also, Baislye et. al reported that using cloths or cotton wool for menstrual hygiene is also a single most predictive for bacterial vaginosis infection(6) (7).…”
Section: Introductionmentioning
confidence: 99%